Blasted literature : Victorian political fiction and the shock of modernism - Ó Donghaile, Deaglán (Edinburgh critical studies in Victorian culture., 2011)
Dynamite novels meet highbrow modernism via the impact of terrorism. Between 1880 and 1915, a range of writers exploited terrorism's political shocks for their own artistic ends. Drawing on late-Victorian 'dynamite novels' by authors including Robert Louis Stevenson, Tom Greer and Robert Thynne, radical journals and papers, such as The Irish People, The Torch, Anarchy and Freiheit, and modernist writing from H.G. Wells and Joseph Conrad to the compulsively militant modernism of Wyndham Lewis and the Vorticists, Ã₃ Donghaile maps the political and aesthetic connections that bind the shilling shocker closely to modernism. Key Features. Extensive original archival research from libraries in the UK, Ireland and the US The first book to examine types of political and literary disruption Detailed discussion of Wyndham Lewis's avant-garde Vorticist journal BLAST in chapter 4